A low‐profile quad‐port UWB MIMO antenna using defected ground structure with dual notch‐band behavior. Issue 9 (29th May 2020) - Pannu, Preeti; Sharma, Devendra Kumar
Abstract: A compact (45 × 45 × 1.6 mm 3 ) ultrawide‐band (UWB), multiple‐input multiple‐output (MIMO) design using microstrip line feeding is presented. The proposed design comprises four elliptical monopoles placed orthogonally on a cost‐effective FR‐4 substrate. In order to improve the impedance bandwidth and lessen the return loss of the MIMO antenna, defects in ground plane are created by etching symmetrical square slots and half‐rings. Moreover, a different method (of unsymmetrical H‐shaped slot with C‐shaped slot) was proposed into the patch to introduce dual‐band rejection performance from UWB at center frequency 5.5 GHz (covering lower WLAN as well as upper WLAN) and 7.5 GHz (X band). In addition, a stub is introduced at the edge of each defected ground structure to obtain isolation >–22 dB covering entire performing band from 2 to 16.8 GHz (where, S 11  < –10 dB). The proposed design has miniaturized size, very low envelop correlation coefficient less than 0.1, stable gain (2‐4 dBi except for notch bands). Furthermore, various MIMO performance parameters are within their specifications, such as diversity gain (= 10 dB), total active reflection coefficient (<–5 dB, and channel capacity loss (<0.35 bits/s/Hz). The presented design is optimized using the HFSS software, and fabricated design is tested using vector network analyzer. The experimental results are in good agreement with the simulation results.